CORRELATION OF GATA-3, E-CADHERIN, P53 AND KI-67 EXPRESSION WITH HISTOLOGICAL TYPE/MOLECULAR SUBTYPE AND CLINICOPATHOLOGICAL PARAMETERS IN BREAST CANCER - Yeliz ARMAN KARAKAYA (Rojan GÜMÜŞ, 2021)
The purpose of our study is to examine immunohistochemically the correlation of GATA binding protein 3 (GATA3), E-cadherin, p53 and Ki-67 expression with histological type/molecular subtype and clinicopathological parameters in breast cancer. Methods and results 120 patients diagnosed with breast cancer were retrospectively investigated between 2018 May and 2021 January. We used the GATA3, E-cadherin, P53, Ki67 antibody by immunohistochemical analysis in breast tumors. GATA3 was positive in 100% (107/107) of the luminal A, luminal B and HER2 overexpressing groups and 79.9% (10/13) of the triple negative (TN) group. It is less common in the TN group (p <0.005). Ki67 of >20% was higher in human epidermal growth factor receptor 2 (HER2) overexpressing and TN groups compared to luminal A and luminal B subtypes (p <0.05). Estrogen receptor (ER) and progesterone receptor (PR) were more frequently observed in the group with Ki67≥20% than that with Ki67 <20% (71/120, 59.2%) (p = 0.024). ER/PR hormone receptors were observed more in the p53-negative group than in the p53-positive group (66/117, 56.4%) (p=0.037). There is no significant difference between molecular subtypes in terms of the incidence of e-cadherin and p53 immunoexpressions (p> 0.05). Conclusions Our study demonstrated that the presence of GATA3 was found to be associated with the ER/PR receptor and tumors associated with these receptors, lumen type breast carcinomas. In addition to its proper use for diagnostic purposes in routine surgical pathology, GATA3 will have a developmental role in breast carcinomas and prognostic significance in different molecular subtypes of tumors at the same clinical stage. Ki67 is observed at a higher rate in high-grade tumors and has a prognostic significance. No significant correlation was reported between e-cadherin and p53 and prognostic factors.